2020
DOI: 10.1093/ageing/afaa249
|View full text |Cite
|
Sign up to set email alerts
|

STOPPFall (Screening Tool of Older Persons Prescriptions in older adults with high fall risk): a Delphi study by the EuGMS Task and Finish Group on Fall-Risk-Increasing Drugs

Abstract: Background Healthcare professionals are often reluctant to deprescribe fall-risk-increasing drugs (FRIDs). Lack of knowledge and skills form a significant barrier and furthermore, there is no consensus on which medications are considered as FRIDs despite several systematic reviews. To support clinicians in the management of FRIDs and to facilitate the deprescribing process, STOPPFall (Screening Tool of Older Persons Prescriptions in older adults with high fall risk) and a deprescribing tool w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
123
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 141 publications
(153 citation statements)
references
References 20 publications
3
123
0
5
Order By: Relevance
“…Furthermore, β-blocker users had a lower fall risk in our cross-sectional analysis (OR 0.86 [0.79-0.95]) in line with the meta-analysis of adjusted data (OR 0.88 [0.80-0.97], 8 studies) [8]. Finally, proton pump inhibitor use was associated with a higher risk only in a cross-sectional analysis and it should be noted that the vast majority of the European expert panel did not considered proton pump inhibitors to increase fall risk in a consensus effort [35]. This indicates that the found association might be explained by the residual confounding.…”
Section: Discussionsupporting
confidence: 52%
“…Furthermore, β-blocker users had a lower fall risk in our cross-sectional analysis (OR 0.86 [0.79-0.95]) in line with the meta-analysis of adjusted data (OR 0.88 [0.80-0.97], 8 studies) [8]. Finally, proton pump inhibitor use was associated with a higher risk only in a cross-sectional analysis and it should be noted that the vast majority of the European expert panel did not considered proton pump inhibitors to increase fall risk in a consensus effort [35]. This indicates that the found association might be explained by the residual confounding.…”
Section: Discussionsupporting
confidence: 52%
“…In persons with AD, AEDs are mainly used for central neuropathic pain, 6 and neuropsychiatric symptoms of cognitive disorders (eg, agitation and aggression), 7 although, particularly in the case of neuropathic pain, this goes against recent recommendations due to an increased risk of falls. 8 Moreover, in a recent systematic review of randomized controlled trials, valproate showed no benefit in treating dementia-related agitation and a high rate of adverse effects, including sedation was observed among valproate users. 9 Still, the risk-benefit profile of most AEDs in persons with AD is still largely unclear [10][11][12][13] and their adverse effects, including effects on cognition are of concern, given that cognitive status is already impaired due to AD itself.…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians and medical students have reported limited self-efficacy in deprescribing [ 79 ], warranting further education on deprescribing and deprescribing tools. These include The American Geriatrics Society Choosing Wisely Workgroup’s publications, the updated Beers Criteria®, the FORTA (Fit fOR The Aged) List, the Screening Tool of Older People's Prescriptions and Screening Tool to Alert to Right Treatment (STOPP/START) criteria, and the Screening Tool of Older Persons Prescriptions in older adults with high fall risk (STOPPFall) [ 80 85 ]. In our view, the learning outcomes of medical students should include knowledge of deprescribing tools and of age- and frailty-related changing risk management and treatment goals.…”
Section: Discussionmentioning
confidence: 99%